Issues and challenges of Cyclone Preparedness Programme (CPP) volunteers: the case of CPP, Dacope, Khulna - Khan, Md. Harun-Or-Rashid (BARC University, 2018)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2017.